The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1016/j.lfs.2018.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Lentivirus-mediated klotho up-regulation improves aging-related memory deficits and oxidative stress in senescence-accelerated mouse prone-8 mice

Abstract: The present study provides a novel approach for klotho gene therapy and demonstrates that direct up-regulation of klotho in the brain might improve aging-related memory impairments and decrease oxidative stress. The underlying mechanism of this effect likely involves the inhibition of the Akt/FoxO1 pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 28 publications
2
33
0
1
Order By: Relevance
“…These aged macaque monkeys exhibited traits similar to those of human patients with Alzheimer's disease ( 26 , 27 ). It was recently demonstrated that gene therapy via Clustered Regularly Interspaced Short Palindromic Repeats technology increased the expression of Klotho, which improved the cognitive ability of experimental mice ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…These aged macaque monkeys exhibited traits similar to those of human patients with Alzheimer's disease ( 26 , 27 ). It was recently demonstrated that gene therapy via Clustered Regularly Interspaced Short Palindromic Repeats technology increased the expression of Klotho, which improved the cognitive ability of experimental mice ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…The confirmation of oxidative stress increase with age of diverse organisms, and the generation of transgenic invertebrates overexpressing the antioxidant enzymes with increased lifespan were among the most important results of these studies 3639. Nevertheless, there were no alterations in the lifespan in most of the examined mouse models, which under- or overexpressed a wide variety of genes coding for antioxidant enzymes 4042. Thus, the role of oxidative stress in aging mammals is not fully understood and still demands further inquiries 43,44…”
Section: Introductionmentioning
confidence: 99%
“…Since it has been shown previously that overexpression of full-length α-Klotho affects neurogenesis (Zhou et al, 2018), we tested whether human secreted Klotho expressed in CA1 neurons enhances pluripotency in the SGZ (Laszczyk et al, 2017). Several transcription factors have been described that can be utilized to evaluate the state of newly developed cells (Salech et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For example, transgenic mice with systemic overexpression of Klotho-VS, a lifespan-extending variant of the human klotho gene, have been found to age-independently perform better than control mice in Morris water maze and Y-maze tests (Dubal et al, 2014), two tests that evaluate spatial memory. Another study found that overexpression of secreted Klotho in response to infection of neurons by intraventricular injection with a lentivirus-based expression system significantly improved the performance of SAMP8 mice in the Y-maze task (Zhou et al, 2018). Surprisingly, peripheral administration of a recombinant α-Klotho fragment (KL1+KL2) was found to be sufficient to enhance memory performance in the Morris water maze and Y-maze in young, aging, and transgenic α-synuclein mice (Leon et al, 2017), even though this fragment does not cross the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%